Keys to Expanding the Rural Healthcare Workforce in Kyrgyzstan - Fonken, Paul; Bolotskikh, Inna; Pirnazarova, Gulzhakhan Fazylovna; Sulaimanova, Gulnura; Talapbek kyzy, Shirin; Toktogulova, Aelita (Frontiers in Public Health, 2020)
Objective/Background: This study assessed Kyrgyzstan’s progress with developing its rural primary care workforce and prioritized next steps to build on its current momentum. Kyrgyzstan has improved rural health care since 1997 through the implementation of family medicine, retraining of rural doctors and nurses, and other efforts. Attrition, emigration, urbanization and population growth are threatening these hard-won advances. In response, it is now educating family medicine residents at rural sites and improving salaries. This study explores other steps to strengthen rural health care in Kyrgyzstan, especially its rural generalists. Methods: This was an observational study using a two-phase survey process. To access the current status of Kyrgyzstan’s rural health care system, we surveyed key stakeholders within that system using a draft version of the new World Health Organization Rural Pathways Checklist. To prioritize next steps, we asked rural FM residents to rank the relative importance of 31 possible future actions to support Kyrgyzstan’s rural primary care workers. Results: Doctors and nurses involved in teaching rural health workers identified that Kyrgyzstan has made good progress with rural professional support and upskilling of existing health workers through education. They saw the least progress with selection of health workers and monitoring. The rural family medicine residents’ top ten suggestions for rural recruitment and retention all involved improving working conditions (providing housing, internet, basic medical equipment, protected time off, better salaries and more respect) and improving clinic efficiency (switching clinic scheduling from walk-in based to appointment based, optimizing the roles of clinical team members and decreasing low-value clinic visits). Conclusions: The WHO Rural Pathways Checklist helped to evaluate Kyrgyzstan’s current efforts to promote rural primary care. The priorities listed above from the next generation of potential rural family doctors could help guide future steps to promote rural health in Kyrgyzstan and the Former Soviet Union.